Proposta de estruturação de um banco de dados e de critérios de priorização para manutenção do sistema viário urbano – SGPU: estudo de caso de Santa Maria - RS - Martins, Márcio da Fonseca (2018)
Due to poor conditions in the asphaltic pavements of the municipality of Santa MariaRS and discontent of population with this situation, the municipal prefecture has shown interest in developing and, in the future, to implement a Urban Pavement Management Systems (UPMS). In this context, the present work sought to elaborate a proposal for structuring a database and prioritization criteria for the maintenance of the Santa Maria-RS urban road system, aiming at the implementation of an UPMS. For this, some steps were taken: definition and characterization of the study area (11 central urban roads); field surveys (traffic counting, survey of pavement defects by means of Continuous Visual Survey – LVC, survey of pavement irregularity using laser inertial profilometer, survey of pavement structural parameters – maximum deflection and radius of curvature –, using Benkelman beam); structuring of the database; elaboration of the traffic diagnosis and the condition of the pavements; proposing a catalog of maintenance solutions and indicating solutions; solutions; standardization of the structured database; proposition of the mathematical model to calculate the Priority Index (PI); creation of prioritization and application scenarios in the standard database; calculation and ranking of IP in each scenario; and, finally, ranking of the sub-brands in each scenario. From the point of view of the diagnosis of the area of study, the lowest NUSACE was registered in Av. Presidente Vargas, towards downtown neighborhood and the largest, at Av. Hélvio Basso, towards downtown. The lowest unidirectional VDM was recorded at Av. João Luiz Pozzobon, towards the center-neighborhood and the largest, at Av. Nossa Senhora Medianeira, towards the center-neighborhood. The ATR in 100% of the floors of the study area was below 10 mm. The best condition of the pavement surface was recorded at Av. Liberdade, neighborhood-center, double lane. The worst condition of the pavement surface was recorded at Av. Governador Walter Jobim, in the neighborhood-center direction. The RC in 77 % of the floors of the study area was greater than 100 meters. The best condition of the pavement structure was registered in Av. Liberdade, direction neighborhood-center, double track. The worst condition of the pavement structure was recorded at Av. Ângelo Bolson, towards downtown. The total value of the solutions was R$ 18.363.546,54. The most expensive route was Av. Governador Walter Jobim and the least expensive, Av. Hélvio Basso. The mathematical model for PI calculation proposed, since it is a simplified and easily understood model, if it is effectively put into practice, can help in the management, at the network level, of the Santa Maria-RS pavements, allowing not only more rational decision making by managers, as well as the optimization of public resources. The best PI predictor was IGGE, followed by D0 corrected, ATR and IRI.